INTELLECTUAL PROCESSING OF HYDROGEOLOGICAL DATA (USING THE EXAMPLE OF GROUNDWATER) (British Journal of Global Ecology and Sustainable Development, 2024)
This comprehensive article delves into the development of an automated information reference hydrogeochemical data bank through the systematization and typification of hydrogeological data using intelligent processing methods and algorithms. It scrutinizes various methods of intelligent analysis of hydrogeological data, emphasizing the importance of understanding general patterns in groundwater chemical composition and predicting changes influenced by anthropogenic factors. The study also focuses on enhancing data presentation to reflect the hydrogeochemical landscape of Uzbekistan. By utilizing data mining techniques and mathematical algorithms, the research aims to delineate geological bodies based on groundwater properties and contamination levels. The article highlights the significance of visualizing results and utilizing data mining tools for decision-making processes. The application of Fisher-type criteria and proximity functions in data analysis further enhances the study's depth and accuracy.